Politisasi Birokrasi - Bantuan Sosial dan Gugatan Perbuatan Melawan Hukum sebagai Sengketa Pemilu - Richo Andi Wibowo (Fakultas Hukum Universitas Islam Indonesia, 2024)
This paper discusses cases of tort committed by government agencies/officials intertwined with election issues. This article raises three questions: by examining court decisions on the so-called Acting Regional Head case, has the tort lawsuit been effective in preventing the politicization of the bureaucracy? Why the previous case had occurred, but no tort lawsuit happened on the politicization of government social assistance?; What needs to be done to make the tort lawsuits more effective in preventing the politicization of bureaucracy and budgets in the future elections? This research examines court decisions and social phenomena with a legal theory as a tool of analysis. This paper concludes that the quality of ratio decidendi and dictum of the Acting Regional Head case were poor; the lawsuit has not been effective in preventing bureaucratic politicization. Moreover, there are several reasons on why nobody has sued tort on the context of politicization of government social assistance: limited time to submit petition; long and bureaucratic tort dispute process; court's narrow interpretation on